Longitudinal relationships between serum ferritin and prognosis among severe community-acquired pneumonia patients - Xu, Jing; Han, Ming-Feng; Ma, Kai-Shu; Zhang, Ting; Wang, Rui-Rui; Zhang, Jing-Jing; Zhao, Hui; Fu, Lin (Frontiers in Pharmacology, 2025)
BackgroundFerritin is one of the major intracellular iron storage proteins and is implicated in the pathophysiological processes of many inflammatory diseases, but its function in community-acquired pneumonia (CAP) was unclear. The purpose of this study was to evaluate the expression of ferritin and analyze the relationship of serum ferritin with CAP.MethodsSevere CAP patients and age- and gender-matched healthy participants were recruited for the study. Serum ferritin was detected through ELISA. Physiological characteristics were recorded.ResultsThe serum ferritin level was significantly increased in severe CAP patients upon initial hospitalization compared to healthy participants, and it decreased after therapy. Correlative analyses hinted that there were obvious relationships of serum ferritin with the indicators of blood routine, liver function, and inflammation. Moreover, linear and logistic regression analyses confirmed that the serum ferritin level was positively related to the scores of CURB-65, CRB-65, and PSI. The poor prognosis including mechanical ventilation, vasoactive agent, ICU admission, death, and longer hospital stays were assessed in severe CAP cases during hospitalization. Multivariate logistic regression showed that higher serum ferritin levels were closely linked to the poor prognostic outcomes.ConclusionThere is significantly positive association between the serum ferritin level upon initial hospitalization with the severity and poor prognosis. Thus, serum ferritin could be an indicator for the determination of severity and prognosis among CAP cases.